Characteristics and quality of freeze-dried mango powder pre-frozen at different temperatures - Capariño, Ofero A. (2000)
Aseptically processed mango puree was first frozen at either -40 C or -65 C using an ultra-low temperature freezer, or at -192 C by direct immersion in liquid nitrogen. All samples were then freeze-dried at a vacuum pressure of 0.001-0.05 Torr.

The times required to reach -40 C, -65 C and -192 C were approximately 278 min (4.5 h), 370 min (6.0 h) and 15 min (0.25 h), respectively. The freezing point of the puree is -2.42 C, lower than the freezing point of water (0 C).

Production of freeze-dried mango powder at an acceptable level of 2-3% moisture content through direct immersion in liquid nitrogen (-192 C) required the shortest drying time of 16 h compared with 18 h freezing at -40 C and 22.5 h at -65 C. There were no significant differences in percent powder recovery among treatments.

Comparison of the physico-chemical properties of the control sample and the reconstituted mango puree produced at -40 C, -65 C and -192 C showed that pH was increased at -40 C but the total soluble solids originally present in the original mango puree (control) was not affected by the freezing method prior to freeze-drying.

Sensory evaluation of the puree indicated no significant differences in aroma, characteristic flavor, sweetness and general acceptability between those of the control and the reconstituted purees. There were no significant differences in color, aroma and general acceptability among the products pre-frozen at -40 C, -65 C and -192 C.
Keywords: Mango, Dried; Mango -- Production